Meningkatkan Keaktifan Belajar Matematika Melalui Teams Games Tournament Berbantuan LKPD Berbasis Budaya Sasak - Pratama, Ridho Yudha; Supiyati, Sri; Hirzi, Ristu Haiban; Nazri, Muhammad (Pendidikan Matematika FKIP Universitas Mataram, 2024)
This study was motivated by the low activeness of students in class VII A SMP Negeri 1 Selong during the mathematics learning process. The purpose of this study was to increase the activeness of mathematics learning using cooperative learning type teams games tournament assisted by Sasak culture-based LKPD on the material of congruence and congruence. This study adapts the Kemmis and McTaggart model of classroom action research which is carried out in 2 cycles, each cycle with 2 meetings. Data collection techniques used in this study are observation, questionnaire, and documentation. Meanwhile, to analyze the data obtained using descriptive statistics. The results of this study indicate that during the pre-cycle the average score of student learning activeness was only 99 or 62%. After implementing cycle I and Cycle II, the average score of students' learning activeness has increased, namely 118 or 73% and 138 or 86%. So that at the end of the cycle it can be said that this class action research was successful with an increase in students' mathematics learning activeness by 24%.